Sentinels of Afghan democracy : the Afghan national army - Chan, Samuel (2009)
Since the fall of the Taliban regime in 2001, the international community has contributed much in terms of manpower, monetary aid, essential equipment and expertise in rehabilitaring this war-torn Central Asia country. The Afghan National Army (ANA) has arguably been one of the leading success stories. This paper explains the current state of the ANA with particular focus on its 'Military Balance', training, and performance in the field. It argues that the ANA in its contemporary ('present' is a better world) state is still not ready to take on responsibility for Afghanistan's security, nor will it be ready in the short-term notwithstanding the progress made thus far. For the ANA to be capable of being sentinels of Afghan democracy, both the Afghans and the international community (and not the Americans alone) must be commmited to work in partnership for many years to come.